Challenges and Opportunities in Developing Stroke Rehabilitation Technologies in the Visayas Region: A Local Regional Perspective (Recoletos Multidisciplinary Research Journal, 2025)
Background: This research examines the challenges and opportunities in stroke rehabilitation technologies, focusing on cost, affordability, and patient accessibility. It also investigates the complex healthcare issues in the Visayas region of the Philippines, including healthcare worker shortages, pay disparities, resource limitations, and limited access to care in remote areas. Methods: The study explores the experiences of medical professionals regarding stroke care and technology use in the Visayas and looks into household caregiver practices, self-management, funding, and policies.Results: Results indicate that mobility difficulties, balancing problems, and limb weakness are major obstacles for patients. Only 33% of respondents receive rehabilitation treatments, highlighting a significant deficiency. Health and community service staff face heavy workloads, serving a larger population than usual. Conclusion: This paper explores technological advances that could revolutionize stroke rehabilitation in regions like the Visayas. Gaining detailed information will enhance understanding of specific needs, enabling tailored interventions to improve outcomes. Integrating telemedicine, VR platforms, robotic devices, and wearable sensors can address accessibility challenges and facilitate patient-specific rehabilitation.
Keywords: healthcare; health professionals; rehabilitation; stroke; technology